Trigger Factors for Stroke in Young Adults: A Case-Crossover Study. (3rd January 2023) - Ekker, Merel S.; Verhoeven, Jamie I.; Rensink, Karlijn M.L.; Schellekens, Mijntje M.I.; Boot, Esther M.; van Alebeek, Mayte E.; Brouwers, Paul J.A.M.; Arntz, Renate M.; van Dijk, Gert W.; Gons, Rob A.R.; van Uden, Inge W.M.; den Heijer, Tom; et al.
Abstract : Background and Objectives: Causes of stroke in young adults differ from those in the elderly individuals, and in a larger percentage, no cause can be determined. To gain more insight into the etiology of (cryptogenic) stroke in the young population, we investigated whether trigger factors, such as short-lasting exposure to toxins or infection, may play a role. Methods: Patients aged 18–49 years with a first-ever ischemic stroke or intracerebral hemorrhage (ICH) in 17 participating centers in the Netherlands completed a questionnaire about exposure to 9 potential trigger factors in hazard periods and on a regular yearly basis. A case-crossover design was used to assess relative risks (RRs) with 95% confidence intervals (95% CIs) by the Mantel-Haenszel case-crossover method, for any stroke (ischemic stroke and ICH combined) and for different etiologic subgroups of ischemic stroke. Results: One thousand one hundred forty-six patients completed the questionnaire (1, 043 patients with an ischemic stroke and 103 with an ICH, median age 44.0 years, 52.6% men). For any stroke, an increased risk emerged within 1 hour of cola consumption (RR 2.0, 95% CI 1.5–2.8) and vigorous physical exercise (RR 2.6, 95% CI 2.2–3.0), within 2 hours after sexual activity (RR 2.4, 95% CI 1.6–3.5), within 4 hours after illicit drug use (RR 2.8, 95% CI 1.7–4.9), and within 24 hours after fever or flu-like disease (RR 14.1, 95% CI 10.5–31.2; RR 13.9, 95% CI 8.9–21.9). Four trigger factors increased the risk of other determined and cryptogenic ischemic stroke, 3 that of cardioembolic stroke, 2 that of large vessel atherosclerosis and likely atherothrombotic stroke combined and stroke with multiple causes, and none that of stroke due to small vessel disease. Discussion: We identified cola consumption, vigorous physical exercise, sexual activity, illicit drug use, fever, and flu-like disease as potential trigger factors for stroke in the young population and found differences in the type and number of trigger factors associated with different etiologic subgroups of ischemic stroke. These findings might help in better understanding the pathophysiologic mechanisms of (cryptogenic) stroke in the young population.